2015
DOI: 10.1002/cjoc.201400899
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorous‐Based Pillar[5]arenes for Uranyl Extraction

Abstract: One phosphine oxide-based pillar [5]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 56 publications
0
1
0
1
Order By: Relevance
“…It was found that the P–Fe–CMK-3 adsorbent had higher adsorption affinity toward UO 2 2+ as compared to the other heavy metals. This selectivity was contributed by several factors such as (i) HSAB principle which states uranyl is hard acid and prefer to bind hard bases (O over S, N over P), (ii) f orbitals of uranium interact more strongly with donor ligands than the d orbitals of the heavy metals, (iii) UO 2 2+ competes with H + to bond with either PO or PO – oxygen atoms within phosphonate functional groups. The coordinating ability of neutral PO group arises by the donation of lone pairs of electrons to unoccupied molecular orbitals of UO 2 2+ whereas, negative charge on the PO – group interacts with UO 2 2+ through electrostatic forces, and (iv) UO 2 2+ has a linear structure (OUO) unlike the common heavy metals which exists in their divalent forms (M 2+ ) at low pH except As 5+ , and Cr 6+ which predominantly exists in their anionic forms such as H 2 AsO 4 – and HCrO 4 – , respectively So, due to difference in charge and structure, the linear UO 2 2+ ion could be better accommodated by the phosphonate chelating groups and the mesopores in P–Fe–CMK-3.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the P–Fe–CMK-3 adsorbent had higher adsorption affinity toward UO 2 2+ as compared to the other heavy metals. This selectivity was contributed by several factors such as (i) HSAB principle which states uranyl is hard acid and prefer to bind hard bases (O over S, N over P), (ii) f orbitals of uranium interact more strongly with donor ligands than the d orbitals of the heavy metals, (iii) UO 2 2+ competes with H + to bond with either PO or PO – oxygen atoms within phosphonate functional groups. The coordinating ability of neutral PO group arises by the donation of lone pairs of electrons to unoccupied molecular orbitals of UO 2 2+ whereas, negative charge on the PO – group interacts with UO 2 2+ through electrostatic forces, and (iv) UO 2 2+ has a linear structure (OUO) unlike the common heavy metals which exists in their divalent forms (M 2+ ) at low pH except As 5+ , and Cr 6+ which predominantly exists in their anionic forms such as H 2 AsO 4 – and HCrO 4 – , respectively So, due to difference in charge and structure, the linear UO 2 2+ ion could be better accommodated by the phosphonate chelating groups and the mesopores in P–Fe–CMK-3.…”
Section: Resultsmentioning
confidence: 99%
“…当 pH 值较低时, 零价铁容易被腐蚀, 从而形成铁离子, 同时生成丰富的 H + , 有益于溶液中的加氢反应; 而当 pH 值较高时, 零价铁的表层容易形成铁的氢氧化物, 同样铁的氢氧化物呈现出更进一步的吸附性能 [112,113] . [116,117] . 如图 17(a)所示, 研究了纳 米零价铁以铁氧化物颗粒(包含有纳米零价铁和铁的氧 化物)对铀的去除 [116] , 结果表明不同溶度的铁纳米粒子 对铀的去除效果都非常好, 最终水溶液中的铀溶度都低 于 1 μg/L, 另外文章还报道去除时间很短, 能在 2 min 内达到 90%的去除率.…”
Section: Figure 15unclassified